The Effect of Share Ownership on Firm Value: The Moderating Role of Green Accounting - Setiasih, Ni Putu Eka; Swastika, Komang Debby Narayani; Sari, Putu Widya Purnama (J-MILE adalah jurnal akademik yang ditinjau sejawat (peer-reviewed) yang diterbitkan oleh CV Knowlexa Indonesia, terbit dua kali setahun (biannually) pada bulan April dan Oktober. Jurnal ini menampilkan penelitian teoretis dan empiris di bidang manaj, 2026)
The manufacturing sector in Indonesia has shown a positive trend, supported by increasing production and orders. However, previous studies on the effects of managerial ownership, institutional ownership, and green accounting on firm value (proxied by Tobin’s Q) have yielded inconsistent results. This study examines the influence of managerial and institutional ownership on firm value, with green accounting as a moderating variable, in manufacturing and energy companies listed on the Indonesia Stock Exchange (IDX) from 2021–2023. Using a quantitative approach with panel data regression from 66 firm-year observations, firm value was measured by Tobin’s Q, ownership by share proportions, and green accounting by a dummy variable for ISO 14001 certification or PROPER ratings. The expected findings suggest that managerial and institutional ownership significantly affect firm value, with green accounting moderating this relationship by enhancing transparency and credibility. Overall, the findings provide stronger support for agency theory in the context of managerial ownership than for institutional ownership. The most significant finding is that green accounting's value lies not in stand-alone application, but in the context of ownership structure and the underlying incentives for its adoption. Managerial ownership proves an effective mechanism for aligning interests with shareholders, encouraging green accounting as a value-creation strategy rewarded by the market. Conversely, the monitoring role of institutional ownership appears suboptimal. This implies that ownership structure is a crucial factor in linking sustainability practices to financial performance, offering implications for management, investors, and regulators in integrating sustainability into performance evaluation.